Physical and physiological testing of soccer players - Haugen, T.; Seiler, S. (Sportscience, 2015)
The article wants to answer the question: Why, what and how should we measure? Summary: Monitoring soccer players is important for evaluating individual and collective team behavior during training sessions and games, in addition to informing recovery strategies and load management. Modern micro-technology allows assessment of physical, technical and tactical performance parameters in "real-world" conditions. However, physical testing performed either in laboratories or on the pitch is required for individual training prescription, and to develop performance benchmarks for playing standards and playing positions. Anaerobic actions precede the majority of goals, and a large number of linear or repeated sprint tests with or without direction changes have been used in order to assess soccer players` ability to create or close a gap. The Yo-Yo tests evaluate the players` ability to repeatedly perform intense exercise. These tests have substantial correlations with high-intensity running distance covered in matches and are considered more valid than measures of maximal aerobic power. Commonly used change-of-direction tests do not mimic on-field movements, and the usefulness of repeated-sprint tests can be questioned, owing to the near-perfect relationship between best and average sprint times. In this presentation we outline minimum standards, percentiles, methodological concerns and future recommendations which hopefully can serve as bottom line information for soccer practitioners.